Survey of Attitudes of Hospital Staff to Cadaveric Kidney Transplantation - Crosby, David L. (1972)
A survey of attitudes showed that apprehensions about the practical implications of cadaveric kidney transplantation were common in doctors and nurses in two acute general hospitals. It also indicated that lack of awareness about potentially suitable donors may be a contributing factor to the existing shortage of donor kidneys.